Model Pembelajaran Berbasis Proyek: Peran Kurikulum Merdeka Dalam Meningkatkan Kreativitas Siswa Sekolah Menengah Kejuruan (SMK) - Delta Panjaitan; Indah Sagita Siahaan; Shandy Nainggolan; Sabrina Nainggolan; Sasta Olivia Damanik; Gayus Simarmata (Young Journal of Social Sciences and Humanities, 2026)
Amidst the shifting paradigm of the global industry, creativity has mutated from a mere supplementary skill into a primary modality for Vocational High School (SMK) graduates to navigate the uncertainties of the labor market. However, a sociological gap persists between the idealism of industrial demands and the reality of vocational learning, which is often ensnared in rigid skill mechanization. This study aims to analyze the implementation of the Kurikulum Merdeka (Independent Curriculum) through the Project-Based Learning (PjBL) model as an instrument to reconstruct student creativity. Utilizing a mixed-methods approach, this study evaluates the interaction dynamics between curricular autonomy, the teacher's role as a facilitator, and student engagement in contextual projects. The findings indicate that although the Kurikulum Merdeka provides extensive space for flexibility, the enhancement of student creativity does not occur automatically; rather, it relies heavily on the ability of educational actors to engage in "creative negotiation" amidst infrastructural constraints and the barriers of a passive learning culture. Theoretically, this study asserts that creativity in vocational schools is a result of the dialectic between open curriculum design and a learning ecosystem that supports risk-taking. These results contribute to the development of vocational learning models that are not merely oriented toward administrative compliance but toward strengthening the transformative inventive power of graduates.